STRATEGI BUSTON CONSULTING GROUP DALAM MEWUJUDKAN PENDIDIKAN ISLAM PEDULI LINGKUNGAN - Erliyanto, Mohammad (CV. Jendela Gagasan, 2025)
The widespread environmental crisis demands a strategic approach in Islamic education to instill environmental awareness in students. The Strategic Boston Consulting Group (BCG) model offers a framework that can be adapted in the management of environmental education programs in Islamic education institutions. This research aims to develop a strategic framework that combines the BCG model with Islamic values in managing environmental programs. This research uses a qualitative method with alibrary research approach, which involves analyzing literature related to the BCG model, Islamic education, and environmental management. The results show that the application of the BCG model allows managers to identify and prioritize effective environmental programs, by categorizing programs in star, cash cow, question mark, and dog components. The implementation of this strategy proved to be able to increase students' ecological awareness, strengthen the relevance of Islamic values with environmental insights, and encourage the creation of a sustainable school culture.